Types de formants dans la dérivation fonctionnelle polonaise et roumaine : bases théoriques - Czarnecki, Szymon (Studia Romanica Posnaniensia, 2020)
The paper describes types of derivational formatives in Polish and Romanian functional, i.e. synchronic derivation, focusing on the proper derivation (i.e. derivation from single-word bases). The proper derivation is positioned as a type of word-formation and a branch of morphology. The author identifies the primary functions of derivational formatives: the semantic, pragmatic and syntactic function. The formatives are identified using a methodology developed in Polish word-formation theory, especially within nest derivatology. Applying a methodology developed for the description of the Polish word-formation system is aimed at distinguishing derivational formatives in Romanian. The author identifies and classifies the following types of derivational formatives in Romanian: affixes (among these prefixes, suffixes, postfixes and ambifixes), alternants (defined as members of alternation), negative formatives (in backformation), paradigmatic formatives (defined as changes in inflexional paradigm), zero formative and accentual formatives. The author also suggests including the types of word-formation stems in the description of the formal structure of derivatives.